2001
DOI: 10.1128/jvi.75.16.7410-7419.2001
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a Functional Duck Hepatitis B Virus Replication Initiation Complex from Separate Reverse Transcriptase Domains Expressed in Escherichia coli

Abstract: Hepatitis B viruses replicate through reverse transcription of an RNA intermediate, the pregenomic RNA (pgRNA). Replication is initiated de novo and requires formation of a ribonucleoprotein complex comprising the viral reverse transcriptase (P protein), an RNA stem-loop structure () on the pgRNA, and cellular proteins, including the heat shock protein Hsp90, the cochaperone p23, and additional, as yet unknown, factors. Functional complexes catalyze the synthesis of a short DNA primer that is templated by and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 42 publications
4
59
0
Order By: Relevance
“…Both TP and RT domains served as a primer to initiate DNA synthesis. Independent TP and RT domains are known to trans-complement each other to carry out the protein priming reaction using the TP domain as a protein primer to initiate DNA synthesis (1,25,27). When the priming reactions were carried out in the presence of Mn 2ϩ , which is known to stimulate priming relative to Mg 2ϩ (27), we found, surprisingly, that the RT domain, as well as TP, acted as a protein primer for initiating DNA synthesis (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Both TP and RT domains served as a primer to initiate DNA synthesis. Independent TP and RT domains are known to trans-complement each other to carry out the protein priming reaction using the TP domain as a protein primer to initiate DNA synthesis (1,25,27). When the priming reactions were carried out in the presence of Mn 2ϩ , which is known to stimulate priming relative to Mg 2ϩ (27), we found, surprisingly, that the RT domain, as well as TP, acted as a protein primer for initiating DNA synthesis (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Both the TP and the RT domains are essential for RT-ε interaction and protein priming but the RNase H domain is dispensable (10,23,33,51). Also, isolated TP and RT domains, when combined together, are able to reconstitute a functional RT protein that is able to carry out protein priming in a trans-complementation reaction (1,23,25,27). Protein priming can be further subdivided into two different stages, requiring distinct RT conformations, the initial covalent attachment of the first nucleotide of the minus-strand DNA (a dGMP in DHBV) to RT (to the primer Y) called initiation and the subsequent addition of the remaining 2 to 3 nucleotides to the initiating nucleotide called polymerization (27,54).…”
mentioning
confidence: 99%
“…A Tyr residue in the terminal protein (TP) domain of P protein acts as acceptor for the first dNTP of a short e-templated oligonucleotide. This "protein-priming" reaction, which for DHBV can be reconstituted completely in vitro (7)(8)(9)(10), establishes a 5′-phosphotyrosyl linkage between P protein and DNA which is maintained during the formation of complete minus-strand DNA (Fig. 1B), RNA-primed synthesis of usually incomplete plus-strand DNA, and circularization into RC-DNA via a short terminal redundancy (r) in the minus strand.…”
mentioning
confidence: 99%
“…The DHBV P protein has shown RDDP activity without o motif. Recent studies have proposed that some chaperones might be needed for RDDP activity at the start point of DHBV replication (Beck and Nassal, 2001). The RDDP activity of our DHBV P protein was very weak compared with DDDP activity and the HBV P protein did not have RDDP activity.…”
Section: Discussionmentioning
confidence: 99%
“…The P proteins were purified through Ni-NTA resin (Qiagen, Germany) by His-6X fusion tag and had DNA-dependent DNA polymerase activity compared with Klenow polymerase. A recent study revealed that the viral P protein interacts with some cellular chaperones in the host during the viral life cycle (Beck and Nassal, 2001;Park and Jung, 2001). The present study offers a method measuring possible new chaperone effects on P protein activity.…”
Section: Introductionmentioning
confidence: 99%